Nikkei: estrangeiro em seu país natal? um estudo sobre identidade, estigma e preconceito com filhos e netos de imigrantes japoneses - Haga, Elizabeth Yuko (2018)
The aim of the present study was to investigate whether the children and grandchildren of Japanese immigrants in Brazil feel or have ever felt like victims of discrimination, prejudice or stigmatization due to their origins. The secondary goals were to assess whether they identified more with Brazilian or Japanese culture, and whether there were differences in these feelings between the children and grandchildren. To this end, 31 people were interviewed (22 women and 9 men), of which 13 were children and 18, grandchildren, between 50 and 65 years old. Participants were recruited through the researcher’s online social networks. The method was qualitative and quantitative. The results were categorized and analyzed using the analytical psychology framework and some constructs from the social sciences. The results showed that the participants experienced discrimination in their childhood and youth, and ambiguity regarding their bicultural roots, with possibilities of working these conflicts at the present time. There were no differences between genders or generations